Eutanásia e dignidade da pessoa humana:uma abordagem jurídico-penal - Nobrega Filho, Francisco Seraphico Ferraz da (2010)
The permanent advance of medicine has constantly expanded the discussion on the transition which separates life and death. The possibility to influence the death process by artificial ways and to elect his moment and shape conduct to the euthanasia theme, an expression of complex meaning, generating a series of occurrences that require explanation. The issue reveals the confluence of several subjects, including the repercussion in the Law fields, causing rare situations until now. This present study aims to approach the euthanasia theme under the legalcriminal optics. For this, will be initially considered the questions related to life and death and the conceptual changes occurred in the last decades, passing to the contextualization of different ways of euthanasia used by scholars and their application from the optics of comparative law. Continuous act, will be performed an analysis of the bioethical principles (justice, charity, nonmaleficence and autonomy) and the balance between the right to a dignified death, derived from human dignity, and the right to life, both with constitutional base. The research is finalized with a study legal-criminal, under the spectrum of Federal Constitution and the Penal Code, from the various euthanistic modalities.